Analysis of antioxidant properties of dibenzylideneacetone derivatives using quantum chemical parameters of the molecule - E. T. Oganesyan; V. M. Rukovitsina; D. I. Pozdnyakov; S. L. Adzhiakhmetova (Фармация и фармакология (Пятигорск))
The antioxidant activity of 10 synthetic dibenzylideneacetone (DBA) derivatives has been studied. Except for the base compound, all other derivatives contain electron-bearing substituents, such as OH and OCH3, on aromatic fragments. Formally, DBA can be considered a system containing a cinnamoyl moiety linked to a substituted styrene residue.The aim of the study was to investigate antioxidant properties of the synthesized DBA derivatives and to analyze their quantum chemical parameters revealing the regularities of the «structure–activity» relationship.Materials and methods. For the carbon atoms of the analyzed compounds, Mulliken charges (AUs), bond numbers (Nms), an unsaturation index (IUA), a free valence index (Fr), a theoretical valence (TV) and the electron density were determined. All calculations were performed on a workstation with an Intel Xeon E5-1620 3.5GHz processor and 20GB RAM using a semi-empirical RM7 method and the WinMopac 2016 software. Ionization energies were calculated using the WinMopac 7.21 software for the studied compounds. The Way2Drug PASS Online predictive program was used to evaluate their possible pharmacological activity. The antioxidant activity was evaluated both in vitro (using DPPH and ABTS assays) and in vivo (by measuring a superoxide dismutase (SOD) activity and the concentration of products reacting with 2-thiobarbituric acid (TBA-AP) in Wistar rats without pathology).Results. A preliminary analysis of the possible types of the biological activity of the synthesized DBA derivatives was performed using the Way2Drug PASS Online program. This analysis showed that all the structures have an antitumor activity, which is apparently due to their antioxidant properties. This type of activity was experimentally confirmed by four tests: by DPPH and ABTS in vitro and the effect on SOD and by the TBA-AP in animals. The analysis of the data allowed us to determine that the most active antioxidants are compounds 5, 6, and 8, which contain phenolic hydroxyl groups. In these compounds, the 8-hydroxy group is surrounded by OCH3 radicals on both sides, making it spatially blocked and, therefore, the phenoxyl radical it forms is the most stable. A comparison of the values of the quantum chemical parameters found shows that the most informative for studying the structure–activity relationship are the Mulliken charges (AUs), electron density on carbon atoms, and also their IUA and Fr.Conclusion. The structural features of the 1,5-diphenylpent-1,4-diene-3-one derivatives and the nature of free radicals formed during biological tests indicate that this class of compounds can be considered promising as antioxidants.